Cephalic measures in normal pre-school children 3 to 7-years of age - A. J. Diament; F. W. Rodrigues (Arquivos de Neuro-Psiquiatria)
In a study designed to determine standards for the Developmental Neurological Examination (DNE) several measures of the head were also recorded. The study consisted in the examination of 200 children, half from each sex, 40 from each age group (3 to 7-years of age). These children were selected among 755 normal pre-school-age children, living in the city of São Paulo (Brazil). The criteria for selection were both anamnestic and clinic. The following measures of the head were recorded: cephalic perimeter, biauricular and antero-posterior distances (Diament, 1967). A new cephalic index (nCI) was also determined (Diament, 1968). This index is useful in detecting changes in head shape mainly in cases of precocious cranioestenosis (Diament, 1968; Facure, 1972). The statistical analysis consisted in determining means and standard errors for each measure. For the new cephalic index it was shown through the Kruskal-Wallis test that there were no significant difference between age and sex. Therefore we considered all groups together to find out the tolerance region for the new index which turned out to be given by the interval: 0.848-1.002. This result is based in 186 cases since 14 were excluded because of some problems in the recording process. Therefore we expect with a confidence of 95% that the above interval covers 90% of the population, in the 3 to 7 years age-groups independently of sex.